Aplikasi Pupuk Bokashi Kotoran Ayam pada Tanaman Jagung Ketan (Zea mays ceratina) - Meriyanto Meriyanto; Miranty Trinawaty; Levi G. Grahana (Jurnal Agroekoteknologi, 2021)
This study aims to assess the response to growth and yield of glutinous corn (Zea mays ceratina) due to various doses of chicken manure bokashi fertilizer. The study used a randomized block design (RBD) with 6 treatments and 4 replications, the treatments given were various doses of chicken manure bokashi fertilizer as follows: P0 = 0 tonnes of bokashi per hectare, P1 = 5 tonnes of bokashi per hectare, P2 = 10 tonnes of bokashi per hectare. hectare hectare, P3 = 15 ton bokashi per hectare, P4 = 20 ton bokashi per hectare, and P5 = 25 ton bokashi per hectare. The variables observed were plant height, number of leaves, leaf area, ear length, ear diameter, ear weight per plant and plant fresh weight. Based on the results of the study, it can be rejected that the provision of chicken manure bokashi fertilizer has a good effect on the growth and yield of glutinous corn, give chicken manure bokashi fertilizer 20 tons per hectare or equivalent to P4 (24 kg per plot) resulting in plant height 269.95 cm, the number of leaves is 14.40, leaf area 26,753.20 cm2, ear length 19.95 cm, ear diameter 4.72 cm, ear weight per plant 271.30 g, and the weight of plant fresh stems is 1,212.05 g.